CORRELATION BETWEEN PRENATAL GENTLE YOGA AND THE ANXIETY LEVEL OF PRIMIGRAVIDA TRIMESTER III PREGNANT WOMEN IN FACING LABOR - Sulistyawati, Luh Putu Bella Octavia; Sriarsih, Ni Gusti Kompiang; Wirata, I Nyoman (Poltekkes Kemenkes Pontianak, 2024)
Anxiety is a common condition felt by pregnant women, especially third trimester primigravida pregnant women, if anxiety is felt excessively and is not immediately overcome, it can cause various complications to trauma for pregnant women and their fetuses. Physical exercise is proven to reduce anxiety felt during pregnancy, one of the recommended physical exercises is Prenatal Gentle Yoga. The purpose of this study was to determine the relationship between prenatal gentle yoga and the anxiety level of third trimester primigravida pregnant women in facing childbirth. The type of research used is correlative analytic with a cross-sectional approach. The sample was 38 pregnant women with data collection using a questionnaire. Data analysis using univariate test and bivariate test. The results of data analysis using rank spearman showed that there was a relationship between prenatal gentle yoga and the anxiety level of pregnant women (p = 0.001), the less the frequency of participation of pregnant women in following prenatal gentle yoga, the higher the level of anxiety that will be felt. For pregnant women primigravida trimester III is expected to follow prenatal gentle yoga more often so that it can help reduce anxiety levels in the face of childbirth.Anxiety is a common condition felt by pregnant women, especially third trimester primigravida pregnant women, if anxiety is felt excessively and is not immediately overcome, it can cause various complications to trauma for pregnant women and their fetuses. Physical exercise is proven to reduce anxiety felt during pregnancy, one of the recommended physical exercises is Prenatal Gentle Yoga. The purpose of this study was to determine the relationship between prenatal gentle yoga and the anxiety level of third trimester primigravida pregnant women in facing childbirth. The type of research used is correlative analytic with a cross-sectional approach. The sample was 38 pregnant women with data collection using a questionnaire. Data analysis using univariate test and bivariate test. The results of data analysis using rank spearman showed that there was a relationship between prenatal gentle yoga and the anxiety level of pregnant women (p = 0.001), the less the frequency of participation of pregnant women in following prenatal gentle yoga, the higher the level of anxiety that will be felt. For pregnant women primigravida trimester III is expected to follow prenatal gentle yoga more often so that it can help reduce anxiety levels in the face of childbirth.